The Effect of Transformational Leadership on Openness to Change with Organizational Trust as a Mediation - Farahdiba, Dea; Adhihendra, Brian Gregory (Review of Management and Entrepreneurship, 2025)
This study investigates the mediating role of organizational trust in the relationship between transformational leadership and openness to change. Employing a descriptive quantitative approach, the research utilizes the Partial Least Squares (PLS) method. Data were collected using purposive sampling and analyzed with SmartPLS software. The questionnaire was distributed via Google Forms, allowing broad dissemination across Indonesia, and resulting in 293 respondents participating in the study. The findings indicate that transformational leadership significantly influences employees’ organizational trust, which, in turn, directly enhances their openness to change. However, this study has certain limitations, particularly regarding the sample, which comprises employees exclusively from the banking sector. Transformational leadership, however, is relevant across various organizational contexts. Another limitation lies in the focus on mediation as an indirect effect. The results of this study offer valuable insights for stakeholders in the banking sector, serving as a guideline to enhance employee well-being amidst organizational system changes. This is particularly pertinent given the recent acquisitions among Islamic banks in Indonesia. The study adopts transformational leadership theory to explore its application within the context of Indonesian Islamic banks, focusing on their employees as the study’s primary subjects